If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(x + 3) + 5x = -15 Reorder the terms: -1(3 + x) + 5x = -15 (3 * -1 + x * -1) + 5x = -15 (-3 + -1x) + 5x = -15 Combine like terms: -1x + 5x = 4x -3 + 4x = -15 Solving -3 + 4x = -15 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 4x = -15 + 3 Combine like terms: -3 + 3 = 0 0 + 4x = -15 + 3 4x = -15 + 3 Combine like terms: -15 + 3 = -12 4x = -12 Divide each side by '4'. x = -3 Simplifying x = -3
| 8.1=9.7-0.2x | | 15b+12c=5 | | 45.99+18x+6.75x=144.99 | | 3(x+-3)=144 | | x(x-7)=9x | | 3(-x+9)=144 | | -33=-2(r+6) | | 3(x+3)=144 | | 7y-21-5=-5y+8 | | 1.5(4-x)=1.3(3-x) | | -5(x+1)+4(2x-5)=2(x+2)-8 | | 1.8y^2+144y-1800=0 | | -5(x+1)+4(2x-5)=3(x-4)+10 | | 4.99+18x+6.75x=144.99 | | x+bx+cx= | | 9x+3+2x-9y-8= | | x(x-2)=-8x | | 3(x+20)=155 | | 11=60-16t^2 | | 1.74y-6=0.09 | | 4x+16y=16 | | 5(5x-4)+4=-15 | | 66=12j | | 12a-20b+4= | | (5x^2+2x-6)+(2x^2+2x+15)-(7x^2-14)= | | x+54=5x | | 50-2*[14-18]-7= | | 0=x^3+6x^2-2x-4 | | x(x-6)=6x | | n+x+p=168 | | 0=6x^2+5x-6 | | -4.1(y-1.4)=-6.8 |